2012
DOI: 10.1155/2012/535062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Invasive Brown Marmorated Stink Bug,Halyomorpha halys(Stål), in Mid-Atlantic Tree Fruit Orchards in the United States: Case Studies of Commercial Management

Abstract: Four commercial orchards in the mid-Atlantic region of the United States were surveyed weekly in 2010 and 2011 for the presence of brown marmorated stink bug and the injury caused to both apple and peaches. Among tested sampling techniques, pyramid traps baited with the aggregation pheromone ofPlautia staliScott, methyl-(2E,4E,6Z)-decatrienoate, yielded the most brown marmorated stink bug adults and nymphs, followed by visual observations. Brown marmorated stink bugs began to feed on apples and peaches soon af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
172
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 206 publications
(198 citation statements)
references
References 26 publications
14
172
0
Order By: Relevance
“…Damage to tree fruit in the USA was first detected in Allentown, PA and Pittstown, NJ (Nielsen & Hamilton 2009b). In orchards where BMSB is established, it quickly becomes the predominant stink bug species and, unlike native stink bugs, is a season-long pest (Nielsen & Hamilton 2009b, Leskey et al 2012b-2009, increasing BMSB populations in WV and MD caused lateseason problems to fruit crops (Leskey & Hamilton 2010a). In southern PA and VA, BMSB was not a recognized pest until the 2010 season.…”
Section: Pest Statusmentioning
confidence: 99%
“…Damage to tree fruit in the USA was first detected in Allentown, PA and Pittstown, NJ (Nielsen & Hamilton 2009b). In orchards where BMSB is established, it quickly becomes the predominant stink bug species and, unlike native stink bugs, is a season-long pest (Nielsen & Hamilton 2009b, Leskey et al 2012b-2009, increasing BMSB populations in WV and MD caused lateseason problems to fruit crops (Leskey & Hamilton 2010a). In southern PA and VA, BMSB was not a recognized pest until the 2010 season.…”
Section: Pest Statusmentioning
confidence: 99%
“…Thought to have been brought over in shipping crates from China, Korea, or Japan, the brown marmorated stink bug began to infiltrate crops in Allentown, Pennsylvania, as early as 1996 and has since spread to at least 33 states in the contiguous United States (Welty et al, 2008;Leskey et al, 2012a). During a population explosion in 2010, Pennsylvania, New Jersey, Delaware, Maryland, West Virginia, and Virginia documented large H. halys populations and severe crop damage (Leskey et al, 2012b), and established populations have even been observed as far north as Canada (Fogain and Graff, 2011). Established populations of this pest have also been discovered in Switzerland and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Kuhlar et al found as many as 20 adult or nymph H. halys on a single ear of sweet corn (Kuhar et al, 2012). With the passing of the Food Quality and Protection Act in 1996, broadspectrum insecticides, which previously were successful in combating native stink bug populations, have been regulated such that they are not effective in controlling H. halys (Leskey et al, 2012b). While researchers are still investigating alternatives, H. halys populations may continue to rise as sharply as they did in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report on the toxicity of a commercially available deltamethrin-incorporated LLIN, ZeroFly screen (VestergaardFrandsen, Washington, DC), on an important invasive pest in the United States and Europe, the brown marmorated stink bug, Halyomorpha halys (Stå l) (Hemiptera: Pentatomidae) (Leskey et al 2012b, Rice et al 2014, and explore strategies for the use of the ZeroFly nets in stink bug IPM.…”
mentioning
confidence: 99%